Social multimedia computing: an emergent area of research - Governo, F.; Teixeira, A. A. C.; Brochado, A. (Journal of Creative Communications, 2017)
We survey and analyze the relationship between ‘social media’ landscape and the ‘over-the-top’ film industry and provide a new market overview of how distinctive media platforms are leveraging each other features as part of their business model. With an elevated penetration of mass-market over the top (OTT) services and coexistence of several business models and value chains that need to be proven, our findings suggest that new entrants, to stand apart, will have to experiment new business models and with multimedia integration of content and services; and, unless they establish new niche services to communities of interest it will be difficult for them to differentiate their offerings and survive. Developing a social content network that connects people socially through films can offer media entrepreneurs and the ‘world film’ industry with a stable business model and a new window of opportunity in their competition for market share. By clarifying the boundaries and affordances of distinct OTT and social media platforms, the present research sustains that coupling video streaming and social networking is the future. It further bears that social multimedia computing should be used to capture and leverage the social activity and interaction of users in order to understand the drivers and trends in the film industry. Finally, it provides a direction for online world films.